A Core Outcome Set for nutritional intervention studies in older adults with malnutrition and those at risk: a study protocol - Visser, Marjolein; Mendonça, Nuno; Avgerinou, Christina; Cavdar, Sibel; Cederholm, Tommy; Cruz-Jentoft, Alfonso J.; Kiesswetter, Eva; Siebentritt, Hanna M.; Sieber, Cornel; Torbahn, Gabriel; Volkert, Dorothee (BMC Geriatrics, 2023)
BACKGROUND: Malnutrition (i.e., protein-energy malnutrition) in older adults has severe negative clinical consequences, emphasizing the need for effective treatments. Many, often small, randomized controlled trials (RCTs) testing the effectiveness of nutritional interventions for the treatment of malnutrition showed mixed results and a need for meta-analyses and data pooling has been expressed. However, evidence synthesis is hampered by the wide variety of outcomes and their method of assessment in previous RCTs. This paper describes the protocol for developing a Core Outcome Set (COS) for nutritional intervention studies in older adults with malnutrition and those at risk. METHODS: The project consists of five phases. The first phase consists of a scoping review to identify frequently used outcomes in published RCTs and select additional patient-reported outcomes. The second phase includes a modified Delphi Survey involving experienced researchers and health care professionals working in the field of malnutrition in older adults, followed by the third phase consisting of a consensus meeting to discuss and agree what critical outcomes need to be included in the COS. The fourth phase will determine how each COS outcome should be measured based on a systematic literature review and a second consensus meeting. This will be followed by a dissemination and implementation phase. Patient and Public Involvement (PPI) representatives will contribute to study design, oversight, consensus, and dissemination. CONCLUSIONS: The result of this project is a COS that should be included in any RCT evaluating the effect of nutritional interventions in older adults with malnutrition and those at risk. This COS will facilitate comparison of RCT results, will increase efficient use of research resources and will reduce bias due to measurement of the outcome and publication bias. Ultimately, the COS will support clinical decision making by identifying the most effective approaches for treating and preventing malnutrition in older adults.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Aged; Core Outcome Set; Delphi technique; Endpoint determination; Malnutrition; Meta-analysis; Randomized controlled trials; Review